PENGGUNA PERPUSTAKAAN DI ERA DIGITAL DALAM PERSPEKTIF FENOMENOLOGI - Liliek Soetjiatie (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
This study would like to get an idea of the meaning of informants for library users ( user ) library , virtual library user behavior change and the ideal library is analyzed in depth interview with the student Elektromedical Engineering Program , Dental Nursing , Nursing and Midwifery Health Polteknik Kemenkes Surabaya on campus Surabaya. Informants were taken by purposive sampling technique based on the research objectives . Analysis of the data using a phenomenological perspective , where the subjective meaning of each behavior produces intersubjective interpretation of an event given each subject in this case is the user library as a free persona choice in determining the appropriate necessities of life . This study suggests that there has been a process of formation of system relevance in the process of social interaction . That individuals in this study were students in determining the behavior of his actions as humans living in the modern era have freedom including the use of the library , not lost in cyberspace huforia promising a wealth of information with electronic capabilities possessed , but still need a conventional library which has advantages in different angle.